Effects of abciximab on postresuscitation microcirculatory dysfunction after experimental cardiac arrest in rats - Padosch, Stephan A.; Teschendorf, Peter; Fuchs, André; Valle y Fuentes, Daniela Rocio del; Peter, Christoph; Popp, Erik; Schneider, Andreas; Böttiger, Bernd W.; Walther, Andreas (Resuscitation, 2010)
Background - The term “postresuscitation syndrome” includes among other pathophysiology impaired microcirculation and endothelial leakage. GPIIb/IIIa receptor antagonists like abciximab have been shown to reduce endothelial leakage and to improve microcirculatory disturbances during experimental endotoxaemia where comparably similar endothelial dysfunction has been observed. Previous investigations on postresuscitation endothelial leakage have indicated a possible role of platelets. Therefore, we investigated effects of abciximab on postresuscitation microcirculation applying in vivo microscopy of postcapillary mesenteric venules after experimentally induced cardiac arrest and cardiopulmonary rescuscitation in rats. - Methods - After 6min of cardiac arrest (CA) and cardiopulmonary resuscitation (CPR), male Wistar rats were randomised into two groups (n=10) to receive abciximab (1mg/kg i.v.) or placebo (0.9% NaCl). Sham operated animals (n=10) served as non-ischaemic controls. At 360, 420 and 480min after return of spontaneous circulation (ROSC) in vivo microscopy was performed to assess venular wall shear rate (WSR) and plasma extravasation (PE). - Results - Besides typical signs of severe endothelial leakage in both CA groups, no significant differences between the treatment groups were observed with regard to WSR and PE. - Conclusion - In our study, a distinct postresuscitation microcirculatory splanchnic impairment after CA and successful CPR was observed. However, abciximab had no effects on WSR and PE. Our data does not support a valid resemblance between postresuscitation microcirculatory dysfunction observed in connection with experimental endotoxaemia. Furthermore, our data indicate that mechanisms other than GPIIb/IIIa mediated platelet activation play a role in postresuscitation syndrome. A better understanding of “postresuscitation disease” should enable the development of future therapeutic strategies for cardiac arrest survivors.
Online verfügbar 26 November 2009
Gesehen am 23.06.2023